MITOL/MARCH5 determines the susceptibility of cardiomyocytes to doxorubicin-induced ferroptosis by regulating GSH homeostasis. (December 2021) - Kitakata, Hiroki; Endo, Jin; Matsushima, Hirokazu; Yamamoto, Shoichi; Ikura, Hidehiko; Hirai, Akeo; Koh, Seien; Ichihara, Genki; Hiraide, Takahiro; Moriyama, Hidenori; Shirakawa, Kohsuke; Goto, Shinichi; et al.
Abstract: MITOL/MARCH5 is an E3 ubiquitin ligase that plays a crucial role in the control of mitochondrial quality and function. However, the significance of MITOL in cardiomyocytes under physiological and pathological conditions remains unclear. First, to determine the significance of MITOL in unstressed hearts, we assessed the cellular changes with the reduction of MITOL expression by siRNA in neonatal rat primary ventricular cardiomyocytes (NRVMs). MITOL knockdown in NRVMs induced cell death via ferroptosis, a newly defined non-apoptotic programmed cell death, even under no stress conditions. This phenomenon was observed only in NRVMs, not in other cell types. MITOL knockdown markedly reduced mitochondria-localized GPX4, a key enzyme associated with ferroptosis, promoting accumulation of lipid peroxides in mitochondria. In contrast, the activation of GPX4 in MITOL knockdown cells suppressed lipid peroxidation and cell death. MITOL knockdown reduced the glutathione/oxidized glutathione (GSH/GSSG) ratio that regulated GPX4 expression. Indeed, the administration of GSH or N -acetylcysteine improved the expression of GPX4 and viability in MITOL-knockdown NRVMs. MITOL-knockdown increased the expression of the glutathione-degrading enzyme, ChaC glutathione-specific γ-glutamylcyclotransferase 1 (Chac1). The knockdown of Chac1 restored the GSH/GSSG ratio, GPX4 expression, and viability in MITOL-knockdown NRVMs. Further, in cultured cardiomyocytes stressed with DOX, both MITOL and GPX4 were reduced, whereas forced-expression of MITOL suppressed DOX-induced ferroptosis by maintaining GPX4 content. Additionally, MITOL knockdown worsened vulnerability to DOX, which was almost completely rescued by treatment with ferrostatin-1, a ferroptosis inhibitor. In vivo, cardiac-specific depletion of MITOL did not produce obvious abnormality, but enhanced susceptibility to DOX toxicity. Finally, administration of ferrostatin-1 suppressed exacerbation of DOX-induced myocardial damage in MITOL-knockout hearts. The present study demonstrates that MITOL determines the cell fate of cardiomyocytes via the ferroptosis process and plays a key role in regulating vulnerability to DOX treatment. (288/300) Graphical abstract: Unlabelled Image Highlights: The mitochondrial ubiquitin ligase MITOL is identified as a novel regulator of DOX-induced cardiomyopathy. A knockdown of MITOL in cardiomyocytes reduced GPX4 to induce the accumulation of lipid peroxide, resulting in ferroptosis. The decreased GPX4 was affected by the reduced GSH/GSSG ratio, which was associated with the increased expression of Chac1. Reduction in MITOL promoted susceptibility to DOX toxicity both in cultured cardiomyocytes and murine hearts. Forced-expression of MITOL in cardiomyocytes restored DOX-induced ferroptotic cell death by maintaining GPX4 content.